(untitled) (Proceedings of International Educators Conference, 2023)
This article discusses translation of linguistic means of caressing in English into Uzbek. Translating any linguistic medium requires a linguistic approach to translation. Linguistic approach to translation directly depends on what linguistic means are accepted as a unit of translation. In this article, we will focus on the translation of the English language means of caress into Uzbek.